Quality of Service-Based Medium Access Control Mechanism for Multimedia Traffic in Mobile Ad Hoc Networks - Abdallah Jama, Mubarak (2009)
This thesis describes an investigation on the problem of quality of service (QoS) support in mobile ad hoc networks (MANETs). The decentralized nature of wireless ad hoc networks makes them suitable for a variety of applications where central nodes cannot be relied on. This thesis presents a medium access control (MAC) QoS mechanism for multimedia applications in IEEE 802.11e based MANETs. IEEE 802.11e standard draft includes new features to facilitate and promote the provision of QoS guarantees in wireless networks with a long-term solution based on QoS-architectures. The motivation is driven by the need to support increasing demand of time-sensitive applications such as Voice over IP (VoIP) and video conferencing applications. IEEE 802.11e enhances the Distributed Coordination Function (DCF) and the Point Coordination Function (PCF) of the legacy IEEE 802.11, through a new coordination function: the Hybrid Coordination Function (HCF). Within the HCF, there are two methods of channel access: HCF Controlled Channel Access (HCCA) and Enhanced Distributed Channel Access (EDCA). EDCA operates in infrastructure-less ad hoc mode and is widely used in MANETs, unlike HCCA, which further assures QoS provisioning operates in infrastructure mode in the presence of access points (AP). Recent researches showed that EDCA lacks QoS support of real-time traffic in MANETs due to its contention based medium access method. This thesis takes HCCA QoS provisioning potentials to MANETs by implementing a MAC mechanism in which HCCA is employed on top of EDCA to work in infrastructure-less environment like MANET with the help of multiple channels. The mechanism dedicates a unique receiver-based channel to every mobile node. It will act as virtual hybrid coordinator (VHC) to exercise control over the channel in contention-free manner while maintaining a common channel in which all mobile nodes can exchange broadcast and routing related messages. The mechanism can be easily integrated with existing 802.11 systems without modification to existing protocols while ensuring a level of admission control and resource reservation over the medium. Simulation results indicate that the mechanism significantly improves the overall network throughput by 20% at the saturation point and improves average delay by 20% at the saturation point compared to pure EDCA with or without multiple channels. Even with multi-channel EDCA, our mechanism guarantees better performance in terms of throughput and MAC delay for high priority traffic in MANET. The research contribution on MAC layer can be integrated into a larger framework for QoS support in MANETs, which opens a wide range of further research in QoS provisioning in MANETs and solve QoS multi-layer design and implementation issues.